Understanding the intrinsic piezoelectric anisotropy of tetragonal ABO3 perovskites through a high-throughput study - Fanhao Jia; Shaowen Xu; Shunbo Hu; Jianguo Chen; Yongchen Wang; Yuan Li; Wei Ren; Jinrong Cheng (npj Computational Materials)
Abstract A comprehensive understanding of the intrinsic piezoelectric anisotropy stemming from diverse chemical and physical factors is a key step for the rational design of highly anisotropic materials. We performed high-throughput calculations on tetragonal ABO3 perovskites to investigate the overall characteristics of their piezoelectricity and the interplay between lattice, displacement, polarization, and elasticity. Among the screened 123 types of perovskites, the structural tetragonality is naturally divided into two categories: normal tetragonal (c/a ratio < 1.1) and super-tetragonal (c/a ratio > 1.17), exhibiting distinct chemical features, ferroelectric, elastic, and piezoelectric properties. Charge analysis revealed the mechanisms underlying polarization saturation and piezoelectricity suppression in the super-tetragonal region, which also produces an inherent contradiction between high piezoelectric coefficient d 33 and large piezoelectric anisotropy ratio |d 33/d 31|. Both the polarization axis and elastic softness direction are strongly correlated to piezoelectric anisotropy, which jointly determines the direction of maximum longitudinal piezoelectric response d 33. The validity and deficiencies of the widely utilized |d 33/d 31| ratio for representing piezoelectric anisotropy were reevaluated.